2021
DOI: 10.1002/aenm.202102447
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐MOFs Derived Porous Cu Nanoribbons with Strengthened Electric Field for Selective CO2 Electroreduction to C2+ Fuels

Abstract: The electroreduction of carbon dioxide is a promising strategy to synthesize value‐added feedstocks and realize carbon neutralization. Copper catalysts are well‐known to be active for selective electroreduction of CO2 to multicarbon products, although the role played by the surface architecture is not fully understood. Herein, mesoporous Cu nanoribbons are constructed via in‐situ electrochemical reduction of Cu based metal organic frameworks for the highly selective synthesis of C2+ chemicals. With the mesopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 45 publications
2
60
0
Order By: Relevance
“…7b). Yang et al 124 prepared mesoporous Cu nanoribbons The chemical state of Cu is another important parameter for the CO 2 RR to C 2+ products. During the electroreduction process, the electrodes tend to be reduced to Cu 0 , regardless of the initial states.…”
Section: + Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…7b). Yang et al 124 prepared mesoporous Cu nanoribbons The chemical state of Cu is another important parameter for the CO 2 RR to C 2+ products. During the electroreduction process, the electrodes tend to be reduced to Cu 0 , regardless of the initial states.…”
Section: + Productsmentioning
confidence: 99%
“…7b). Yang et al 124 prepared mesoporous Cu nanoribbons via in situ electrochemical reduction of Cu-MOFs. The mesoporous structure of Cu nanoribbons could concentrate OH − on the surface, which increased the local pH and led to improved selectivity of C 2+ products.…”
Section: Co2rr Catalysts For Different Productsmentioning
confidence: 99%
“…The pore structure can be clearly seen in HAADF–STEM images, due to the porous sites having a darker contrast because of the fewer atoms. For example, Yang et al reported the construction of mesoporous Cu nanoribbons by in situ electrochemical reduction of Cu–based metal organic frameworks [ 57 ]. The HAADF–STEM image revealed that a high density of mesopores was distributed throughout the whole of nanoribbons ( Figure 5 a) as there were many dark pores on the bright Cu nanoribbons.…”
Section: Defects In Metal Nanomaterialsmentioning
confidence: 99%
“…( b ) The corresponding intensity profile along the lines that marked by numbers 1 and 2 with yellow color in ( a ). Reproduced with permission [ 57 ]. Copyright 2021, Wiley–VCH.…”
Section: Figurementioning
confidence: 99%
“…In their work, the cations were concentrated around the sharp tip, leading to an increased local concentration of CO 2 near the active surface for CO 2 RR. The electric field-induced effect on the concentration of reagents around the tips was also analyzed using kinetic simulations, indicating that the electric field-induced aggregation effect can provide additional CO 2 for improving the CO 2 RR performance [134,135]. Recently, Liu's group [136,137] also reported that the high electric field created locally by high-curvature Cu nanoneedle (Cu NN) arrays can optimize *CO adsorption and reduce C−C coupling energy barriers (Fig.…”
Section: Electric Field Effectsmentioning
confidence: 99%